In Memoriam: Dermot McAleese - Walsh, Patrick Paul (Statistical and Social Inquiry Society of Ireland, 2025)
In memoriam of the late Professor Emeritus Dermot McAleese (1942-2025) who served as the 51st President of the Society from 1995 to 1998. Born in Dublin, he was educated at Belvedere College before attending University College Dublin and graduating in commerce and then economics. The initial phase of an academic career first took root in Accra at the University of Ghana from 1964 to 1966. He then proceeded to be awarded a PhD in 1971 at Johns Hopkins University in the United States for a thesis titled ‘Import Demand, Protection and the Effects of Trade Liberalisation on the Irish Economy’.
In Memoriam: Dermot McAleese
Keywords: Dermot McAleese; 314.15